Keterlekatan Budaya dan Ekonomi pada Industri Tahu Rumahan di Kecamatan Arjasa, Jember - Anisa Andiana Wulandari Soemarsono; Hana Vernanda; Lisa Roselawati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research examines the influence of relational embeddedness and social networks on economic behavior in the home-based tofu industry in Arjasa District, Jember. The research focuses on how relational embeddedness influences the acquisition of business capital, work management, and conflict resolution within the business, as well as how home-based tofu industry owners strategize to develop their businesses amidst intense competition by utilizing their social networks. This research employs a qualitative approach with an ethnographic approach. The informants of this research are the owner of the AJ home-based tofu industry, workers who have kinship ties, and workers who do not have kinship ties. Data collection techniques utilize three components: observation, interviews, and documentation.